The SORL1 p.Y1816C variant causes impaired endosomal dimerization and autosomal dominant Alzheimer’s disease - Jensen, Anne Mette G.; Raska, Jan; Fojtik, Petr; Monti, Giulia; Lunding, Melanie; Bartova, Simona; Pospisilova, Veronika; van der Lee, Sven J.; Van Dongen, Jasper; Bossaerts, Liene; Van Broeckhoven, Christine; Dols-Icardo, Oriol; et al. (Proceedings of the National Academy of Sciences - PNAS, 2024)
Truncating genetic variants of SORL1 , encoding the endosome recycling receptor SORLA, have been accepted as causal of Alzheimer’s disease (AD). However, most genetic variants observed in SORL1 are missense variants, for which it is complicated to determine the pathogenicity level because carriers come from pedigrees too small to be informative for penetrance estimations. Here, we describe three unrelated families in which the SORL1 coding missense variant rs772677709, that leads to a p.Y1816C substitution, segregates with Alzheimer’s disease. Further, we investigate the effect of SORLA p.Y1816C on receptor maturation, cellular localization, and trafficking in cell-based assays. Under physiological circumstances, SORLA dimerizes within the endosome, allowing retromer-dependent trafficking from the endosome to the cell surface, where the luminal part is shed into the extracellular space (sSORLA). Our results showed that the p.Y1816C mutant impairs SORLA homodimerization in the endosome, leading to decreased trafficking to the cell surface and less sSORLA shedding. These trafficking defects of the mutant receptor can be rescued by the expression of the SORLA 3Fn-minireceptor. Finally, we find that iPSC-derived neurons with the engineered p.Y1816C mutation have enlarged endosomes, a defining cytopathology of AD. Our studies provide genetic as well as functional evidence that the SORL1 p.Y1816C variant is causal for AD. The partial penetrance of the mutation suggests this mutation should be considered in clinical genetic screening of multiplex early-onset AD families.